High Doses of PDE5 inhibitors and tramadol reversibly alters haematological parameters in rats - Victor U. Nna, Victor O. Oka, Augustine L. Udefa, Emmanuel O. Ofutet, Ofem E. Ofem (Journal of Applied Pharmaceutical Science, 2016)
This study examined the effect of chronic administration of PDE5 inhibitors and tramadol on haematological indices because of their reported high incidence of abuse. Additionally, the possibility of reversal of negative effects following withdrawal of treatment was examined. Fifty male rats (180 - 200g body weight) were grouped into five (n = 10), namely: control, sildenafil, tadalafil, tramadol and sildenafil+tramadol group. The different groups were orally treated with 0.2mL normal saline, sildenafil (1 mg/100gb.w.), tadalafil (1 mg/100gb.w.), tramadol (2 mg/100g b.w.) and sildenafil + tramadol (1 &2 mg/100gb.w. respectively). Treatment was done thrice a week, for 8 weeks and the animals were allowed access to feed and water ad libitum. Five animals were sacrificed per group, while the remaining 5/group continued for another 8 weeks without drug administration (recovery test).Blood samples were collected from each animal via cardiac puncture at the end of both phases for assessment of haematological parameters. Red blood cells (RBC) count, haemoglobin (Hb) concentration, packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), red cell distribution wide standard deviation (RDW-SD), white blood cells (WBCs) count, platelets count, mean platelets volume (MPV) and platelets large cell ratio (P-LCR) were significantly reduced in all the treated groups compared with the control. Following withdrawal of treatment, RBC count, Hb concentration, PCV and red cell absolute values were significantly increased in all recovery groups compared with their respective treated groups. Haematological alterations were reversed following withdrawal of treatment. However, platelet indices were poorly reversed in sildenafil and tramadol recovery groups.
Keywords: Blood cell count, PDE5, sildenafil, tadalafil, tramadol, platelets.